Phenological stage-specific DOM transformations sustain N2 fixation during rice growth in paddy soil - Xiaomin Wang; Xueying Feng; Linhao Liang; Guozheng Gao; Meng Wu; Christina Hazard; Graeme W. Nicol; Baoli Zhu; Rong Sheng; Xiaoyuan Yan; Jun Shan (Soil Biology and Biochemistry, 2026)

Microbial regulation of the molecular succession of dissolved organic matter in paddy soils across rice phenological stages - Xueying Feng; Xiaomin Wang; Meng Wu; Xiaofang Ma; Linhao Liang; Yumeng Zhang; Xiaoyuan Yan; Jun Shan (Applied Soil Ecology, 2026)

The mineral constraint: Energy transition under supply chain bottlenecks and greenflation - Zhuo Feng; Linhao Cui (Journal of Cleaner Production, 2026)

Vertical variation in dissolved organic matter composition regulates bacterial diversity and metabolism in paddy soils - Xueying Feng; Xiaomin Wang; Meng Wu; Xiaofang Ma; Linhao Liang; Xiaoyuan Yan; Jun Shan (Journal of Soils and Sediments, 2026)

The impact of nonlinear surface energy partitioning on potential evapotranspiration: A machine learning study based on FLUXNET data - Weiqi Liu; Shaoxiu Ma; Haiyang Xi; Linhao Liang; Kun Feng; Atsushi Tsunekawa (Agricultural and Forest Meteorology, 2026)

Construction of island ecological security pattern under multi-circle development pattern: Evidence from Hainan Island - Sizheng Li; Feng Gui; Hongyu Li; Yanwei Song; Linhao Peng; Lin Zhou; Yang Wang (Ocean & Coastal Management, 2025)

The evaluation of the suitability of potential evapotranspiration models for drought monitoring based on observed pan evaporation and potential evapotranspiration from eddy covariance - Weiqi Liu; Shaoxiu Ma; Haiyang Xi; Linhao Liang; Kun Feng; Atsushi Tsunekawa (Journal of Hydrology, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Quantitative analysis of the sensitivity and spatial stratified heterogeneity of extreme precipitation across river basins - Ruixin Duan; Linhao Zhong; Guohe Huang; Yongping Li; Feng Wang (Journal of Hydrology, 2024)

Navigating highly reversible Zn metal anodes via a multifunctional corrosion inhibitor-inspired electrolyte additive - Buxin Ma; Kun Zhang; Linhao Li; Renjie Jia; Bingbing Wang; Quan Ji; Xiaojing Long; Jinkui Feng; Liwen Tan (Chemical Engineering Journal, 2024)

Two-sided resource-constrained assembly line balancing problem: a new mathematical model and an improved genetic algorithm - Linhao Feng; Yesong Wang; Xifeng Fang; Hang Yu; Shengwen Zhang (Swarm and Evolutionary Computation, 2024)

Analysis of the water temperature and quality characteristics of the Daheiting Reservoir based on coupled hydrology–hydrodynamic–water quality simulations - Ting Zhang; Linhao Wang; Binxin Xu; Jianzhu Li; Ping Feng (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Nanoscale characterization of Ediacaran microfossils from lower Doushantuo formation chert nodules - Shiqi Cheng; Lianjun Feng; Chaoqun Zhang; Linhao Cui; Wei Liu; Hao Qiu; Shi He; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2024)

The role of atmospheric rivers and associated circulation patterns in the Arctic warming in boreal winter - Zhaohui Gong; Linhao Zhong; Lijuan Hua; Jinming Feng (International Journal of Climatology, 2024)
Atmospheric rivers (ARs) serve a narrow, filamentary channels responsible for intense moisture and heat transport, which are vital for the Arctic sea ice loss and surface air warming, particularly in winter. In this study, ERA5 reanalysis data from 1979 to 2020 are used to investigate the evolution of ARs in the Arctic and the corresponding atmospheric circulation patterns in winter. Our findings indicate that atmospheric circulation is a key factor that facilitates the transport and dispersion of ARs. Cyclonic circulation anomalies provide the dynamical support for ARs in the early development stages, while anticyclonic anomalies are essential for maintaining the thermal and moisture conditions of ARs, particularly after their intrusions into the Arctic region. The cooperation between cyclonic and anticyclonic anomalies plays a critical role in the infiltration and dispersion of ARs, governed by distinct circulation modes for regional intrusions. A positive Arctic Oscillation‐like pattern manifests as a cyclonic system over the Arctic, increasing the likelihood of AR intrusion into Baffin Bay. Conversely, a negative pattern induces a more intense anticyclonic system over the Arctic, thereby raising the frequency of ARs in the Bering Strait. The Pacific‐North American pattern not only directly affects ARs entering the Arctic via the Pacific but also has downstream impacts on ARs intruding the Arctic through Baffin Bay.

Prediction of the soil water content in the Luanhe river basin based on CMIP6 - Ting Zhang; Linhao Wang; Jianzhu Li; Ping Feng (Journal of Cleaner Production, 2023)

Interdecadal aridity variations in Central Asia during 1950–2016 regulated by oceanic conditions under the background of global warming - Linhao Zhong; Lijuan Hua; Yao Yao; Jinming Feng (Climate Dynamics, 2021)

Moisture transport to a typical transitional climate zone in North China forced by atmospheric and oceanic internal variability under the background of global warming - Linhao Zhong; Lijuan Hua; Yao Yao; Jinming Feng; Tianbao Zhao (International Journal of Climatology, 2021)
North Central China (NCC) (34°–42°N, 95°–107°E), a typical transitional climate zone between westerlies and monsoon, shows multiple time‐scale variations in precipitation under the background of global warming. Thus, NCC moisture transport (NMT) was analysed based on reanalysis data from 1979–2015. By using the spatially unbounded dynamic recycling model, main NMT pathways and moisture sources were identified for the summer rainfall of NCC. The trend pattern of NMT manifests as a seesaw pattern with a weakening northwesterly transport but an enhancing southwesterly transport, suggesting an interaction between the mid‐latitude westerlies and the Indian monsoon. The temporal evolution of the NMT trend pattern exhibits interannual and multidecadal variability superimposed on long‐term trends, which correspond to the atmospheric and oceanic physical processes, respectively. The partial least squares regression analysis demonstrated that the temporal evolution of NMT trend patterns can be well explained by atmospheric and oceanic internal climate variability (ICV). At interannual time scales, the atmospheric ICV, composed of the circumglobal teleconnection (CGT) and East Atlantic (EA) and East Atlantic/Western Russia (EAWR) teleconnections, forms a Eurasian wave train that weakens westerly transport via the Europe blocking flow and enhances southwesterly transport via local circulation anomalies with a zonal dipole structure. However, oceanic ICV, composed of the Atlantic Multidecadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO), exerts influence on a multidecadal time scale to decelerate the mid‐latitude westerly jet over the North Atlantic, providing favourable upstream background conditions for the formation of the Europe blocking and further maintaining the atmospheric ICV‐induced Eurasian wave train. Thus, the internal oceanic and atmospheric processes at different time scales couple to contribute to long‐term changes in precipitation over NCC under the background of global warming.

Wind-driven, double-gyre, ocean circulation in a reduced-gravity, 2.5-layer, lattice boltzmann model - Linhao Zhong; Shide Feng; Dehai Luo; Shouting Gao (Advances in Atmospheric Sciences, 2006)

Wind-driven ocean circulation in shallow water lattice Boltzmann model - Zhong Linhao; Feng Shide; Gao Shouting (Advances in Atmospheric Sciences, 2005)